Antihyperlipidemic Effectivity of Sweet Orange Peel Extract (Citrus sinensis) on Triglyceride Levels in Male Mice (Mus musculus) Induced by High Cholesterol - Ellya Catharine Romanna Aprilya Lumbantoruan; Mistika Zakiah; Andhi Fahrurroji (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
Hyperlipidemia is a significant risk factor for atherosclerosis in arteries and cardiovascular disease, especially coronary heart disease (CHD), the leading cause of global mortality. Treatment of hyperlipidemia can be done through chemical treatment. However, statins have potentially dangerous side effects such as myopathy and rhabdomyolysis, so a therapeutic solution with minimal toxicity is needed. One of the potential treatments is Citrus sinensis orange peel, which contains antihyperlipidemic bioactive compounds, namely hesperidin, and naringenin. The aim of this research is to determine the effectivity of sweet orange peel extract (Citrus sinensis) on high cholesterol-induced male mice (Mus musculus) triglyceride levels. Citrus sinensis orange peel was extracted by maceration method using 50% ethanol as solvent. Lipid profile measurements were performed three times using the GPO-PAP method. The concentration of orange peel extract in the treatment group (P1, P2, P3) was 10%, 5%, and 1%. The positive control received 40 mg atorvastatin treatment, the negative control received 1% CMC Na, and the control received abnormal treatment. Antihyperlipidemic therapy with Citrus sinensis sweet orange peel extract has a strong relationship/influence on triglyceride levels in mice. Sweet orange peel extract (Citrus sinensis) has antihyperlipidemic effectiveness in reducing blood triglyceride levels in mice (Mus musculus) induced by high cholesterol. The effective dose is 1% dose.